Beyond Expectations: How Perceived Quality Shapes Satisfaction in Eco-Friendly Accommodations (Journal of Education, Humanities, and Social Research, 2025)
This study examines the determinants of customer satisfaction in eco-themed hotels by analyzing the roles of perceived quality, expectation confirmation, and sustainability attributes, using Hangzhou Xixi Hotel as a case study. Based on data collected from 250 valid questionnaires (after data cleaning and screening), the research employs quantitative analysis through structural equation modeling (SEM) to test hypothesized relationships. Findings reveal that perceived quality of eco-friendly facilities and services directly drives satisfaction (β = 0.460, p < 0.001), while expectation confirmation shows no significant effect (β = 0.007, p > 0.05). Sustainability value is identified as a critical mediator, indicating environmental initiatives enhance satisfaction beyond traditional service quality dimensions. Methodologically, the study validates an adapted SERVQUAL scale for eco-specific quality measurement and uses SEM to confirm construct validity. Practical implications emphasize prioritizing tangible eco-infrastructure investments, aligning expectation management with sustainability outcomes, and leveraging cultural insights for market-tailored strategies. This research advances theoretical understanding of satisfaction in green hospitality and provides actionable guidance for sustainable hotel management.